Calidad de los formatos únicos de atención y su relación con la satisfacción del usuario digitador de la Unidad Desconcentrada Regional de Loreto SIS del año 2024 - Pinedo Mori, Luis (2025)
Although the Comprehensive Health Insurance (SIS) has expanded its coverage in Peru and provides access to health services for vulnerable populations, significant challenges persist in financing management and information systems integration. Therefore, this study aims to identify the relationship between the quality of the Single Care Forms and the satisfaction of data entry users at health facilities within the jurisdiction of the Loreto Regional Decentralized Unit (SIS) in 2024. Using a quantitative observational approach and a non-experimental correlational design, the study included a population of 150 data entry users and a sample of 109 from different health facilities within the jurisdiction of the Loreto Regional Decentralized Unit of Comprehensive Health Insurance. A moderately positive relationship between data entry quality and data entry user satisfaction is confirmed, indicating that better organization and accuracy of the forms improves user perception. Likewise, the quality of records in ARFSISWEB was significantly related to satisfaction, highlighting the need to better structure the data. Furthermore, the absence of material errors in the records was positively related to satisfaction, demonstrating the importance of minimizing these errors. Furthermore, proper preservation of forms was positively correlated with satisfaction, emphasizing the need to improve their storage. In conclusion, optimizing document quality, reducing errors, and implementing preservation and digitization strategies are essential to improving the data entry experience and ensuring efficient information management in the healthcare system.